2012
DOI: 10.1016/j.ccr.2012.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sox9-Dependent Acinar-to-Ductal Reprogramming as the Principal Mechanism for Initiation of Pancreatic Ductal Adenocarcinoma

Abstract: Summary Tumors are largely classified by histological appearance, yet morphological features do not necessarily predict cellular origin. To determine the origin of pancreatic ductal adenocarcinoma (PDA), we labeled and traced pancreatic cell populations after induction of a PDA-initiating Kras mutation. Our studies reveal that ductal and stem-like centroacinar cells are surprisingly refractory to oncogenic transformation, whereas acinar cells readily form PDA precursor lesions with ductal features. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
647
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(716 citation statements)
references
References 58 publications
38
647
1
2
Order By: Relevance
“…These data are supported by reports that the expression of Ngn3 and Hes1 is mutually exclusive in the developing pancreas (27,35), as is the expression of Sox9 and Ngn3 at the endocrine progenitor stage (46,(103)(104)(105). Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106).…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalisupporting
confidence: 71%
“…These data are supported by reports that the expression of Ngn3 and Hes1 is mutually exclusive in the developing pancreas (27,35), as is the expression of Sox9 and Ngn3 at the endocrine progenitor stage (46,(103)(104)(105). Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106).…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalisupporting
confidence: 71%
“…Although the relationship between ER stress and ADM is not well understood, a recent report suggests that ER stress resulting from perturbation of basal autophagy via loss of ATG7 is associated with spontaneous activation of ADM in a mouse model (42). ADM is critical for the initiation of pancreatic tumorigenesis (5,32). In the PKC acinar cells, GRP78 was highly elevated, suggesting that it could play a role in ADM under oncogenic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mutationally activated oncogenic KRAS signals through the PI3K-PDK1-AKT pathway and the canonical mitogen-activated protein kinase pathway via RAF-MEK1/2-ERK1/2, as well as via positive feedback activation of receptor tyrosine kinases engaged by autocrine and paracrine stimuli (3). Although the histological appearance of PDAC suggests a ductal cell of origin, accumulating evidence reveals that PDAC originates primarily through transdifferentiation of acinar cells into ductal cells in a process referred to as acinar-to-ductal metaplasia (ADM), although centroacinar cells and pancreas precursor cells could also give rise to PDAC (2,4,5). To study PDAC, a pancreatic cancer mouse model mimicking human PDAC has been established using the pancreatic and duodenal homeobox 1 promoter-driven Cre-recombinase (Pdx1-Cre) to conditionally activate the Kras lox-stop-lox G12D allele and delete one allele of p53.…”
mentioning
confidence: 99%
“…However, the validity of PDL as a model of endocrine regeneration has now been called into question [5][6][7]11,13,14]. Recent results from PDL in mouse models have shown that some acinar cells can escape death [7] and that acinar compartment can regenerate in a long-term evolution after PDL (over 6 months), probably by restoration of pancreatic drainage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since ADM is characterized by a switch from acinar to ductal phenotype with active proliferation, and since metaplasic ductal lesions are frequently seen in chronic pancreatitis as well as in specimens of pancreatic ductal adenocarcinoma (PDAC), ADM is thought to represent a preneoplastic condition [1,3,4]. Even though some areas of ADM could revert to normal acinar morphology [5,6] in the absence of oncogenic Kras mutations or in the presence of acute pancreatitis, the transition of acinar cells into a duct-like state (as in ADM) has been recognized as an important early event in tumor initiation.…”
Section: Introductionmentioning
confidence: 99%